Cystic lymphangioma of parotid in adult - A rare entity (Indian Journal of Case Reports, 2018)
Cystic lymphangioma of parotid in an adult is a rare occurrence. Very few cases of cystic lymphangioma of parotid have been reported in the literature. Here, we report a case of parotid cystic lymphangioma in a 23-year-old female. Ultrasonography showed a well-defined multicystic lesion with thick internal septations in the parotid region. Fine needle aspiration showed mature lymphocytes only. The diagnosis of cystic lymphangioma of parotid was confined on histopathology. Surgery is the mainstay of treatment; however, medical management in the form of sclerotherapy may be required in infiltrative lesions or when surgical management is not possible. Although rare, cystic parotid lymphangioma should be kept as a differential in cystic lesions of the parotid gland in children as well as adults.